A Fictitious Play Algorithm for Matrix Games with Fuzzy Payoffs - Emrah Akyar (Abstract and Applied Analysis)
Fuzzy matrix games, specifically two-person zero-sum games with fuzzy payoffs, are considered. In view of the parametric fuzzy max order relation, a fictitious play algorithm for finding the value of the game is presented. A numerical example to demonstrate the presented algorithm is also given.